Penyuluhan Bahaya Listrik Dan Kebakaran Rumah Dengan Mengutamakan K3 di Desa Tondegesan 1 Minahasa Sulawesi Utara - Ridwan Ridwan; Nontje Sangi; Billy M. H Kilis; Janne Deiy Ticoh; Putri Maharani (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2023)
There are still many ways to use electrical equipment at home that are used by mothers who are not in accordance with the usage procedures and ethics contained in the general regulations for electrical installations.. The existence of this community service activity has a positive impact on public knowledge and awareness of how to use electricity properly so as to avoid the dangers of electricity and fire. This community service activity took place in Tondegesan 1 Village, where the object of the service was namely housewives and fathers with work activities at home and garden with 25 participants. The method used for this service is in the form of lectures, questions, and answers, and is supported by demonstrating the dangers of electricity and fire through simulations displaying K3 props. The results obtained by this community service, after counseling on the dangers of electricity and fire, 90% of the residents are aware and fully understand the knowledge of the dangers of electricity and fire by knowing the procedures for using K3 facilities and being able to change habits in how to use electricity in a better direction following PUIL as well as according to SNI in the selection of electrical equipment